Creating Observational 3D Sculptures - Badni, Kevin (2015)
Technology has been used to assist in communication and concept development by artists, designers/inventors, engineers, clients, manufacturers and others. [1-3] The use of technology to aid artists capture what they see has been used since the Renaissance with the introduction of the camera lucida and the camera obscura. A modern method to assist in capturing how people see is to use eye tracking technology. The data collected from eye tracking experiments is widely believed to reflect what within the viewing space is being assessed. The analysis of this data can be output in statistical form, or as 2D graphic overlays placed on top of flat images. The innovation described in this paper is the application of a new methodology developed to allow quantitative eye tracking data to be used as a basis to create 3D sculptural forms. This paper is structured with first a brief explanation of eye tracking, leading to the description of the new 3D eye tracking methodology. The results from the test and the final output are reviewed in the analysis including the lessons learned and the possible areas for improvement.